Migrant Perceptions of Their Social Inclusion, Social Networks, and Satisfaction with Life in Northern Spain - Gorka Roman Etxebarria; Naiara Berasategi Sancho; Nahia Idoiaga-Mondragon; Idoia Legorburu Fernandez (Societies, 2024)
This paper aims to analyse the individual perceptions of belonging to social networks among migrants living in northern Spain, exploring various dimensions such as perceived inclusion and life satisfaction. A quantitative analysis was employed with data collected through a survey of 373 migrants from different ethnic backgrounds. The findings indicate that (1) women have higher levels of perceived satisfaction with their life and social networks; (2) young migrants have higher levels of friendship networks; (3) the highest levels of perceived inclusion were found among Central Europeans, followed by individuals from Latin America, Asia, Africa and, finally, Eastern Europe; and (4) each social network under analysis was positively correlated with perceived inclusion and satisfaction with life. In summary, the results emphasise that a greater presence of networks is associated with higher levels of perceived inclusion and life satisfaction.